2020
DOI: 10.14338/ijpt-20-00010.1
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Heart Dose with Protons and Cardiac Substructure Sparing for Mediastinal Lymphoma Treatment

Abstract: Purpose Electrocardiogram-gated computed tomography with coronary angiography can be used for cardiac substructure sparing (CSS) optimization, which identifies and improves avoidance of cardiac substructures when treating with intensity modulated radiotherapy (IMRT). We investigated whether intensity modulated proton therapy (IMPT) would further reduce dose to cardiac substructures for patients with mediastinal lymphoma. Patients and Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…In this respect, current NTCP cardiotoxicity models, which are all developed with photon-based RT techniques, could be misleading when applied to proton therapy. Nevertheless, dosimetric comparison between HL proton therapy and photon techniques (3D or IMRT) demonstrated a significant gain on all cardiac substructures (cardiac cavities, valves, and coronary arteries) [7], and Taparra et al [25] found that the superiority of IMPT over IMRT at the substructure level was conserved even with ECG-gated cardiac substructure sparing (CSS) planning. An example of comparative dosimetry between IMPT and IMRT is provided in Figure 1.…”
Section: Reduction Of Radiation-induced Cardiotoxicitymentioning
confidence: 99%
“…In this respect, current NTCP cardiotoxicity models, which are all developed with photon-based RT techniques, could be misleading when applied to proton therapy. Nevertheless, dosimetric comparison between HL proton therapy and photon techniques (3D or IMRT) demonstrated a significant gain on all cardiac substructures (cardiac cavities, valves, and coronary arteries) [7], and Taparra et al [25] found that the superiority of IMPT over IMRT at the substructure level was conserved even with ECG-gated cardiac substructure sparing (CSS) planning. An example of comparative dosimetry between IMPT and IMRT is provided in Figure 1.…”
Section: Reduction Of Radiation-induced Cardiotoxicitymentioning
confidence: 99%
“…16 Advanced radiation techniques permit significantly increased precision in treatment planning, allowing preferential sparing of various portions of the heart. 17 Understanding the response of specific cardiac substructures to radiation dose may allow prioritization of substructure sparing in treatment planning to reduce long-term burden of disease. Recent reviews of multiple adult malignancies have called for investigation into the relationship between radiation doses to cardiac substructures and late cardiac disease.…”
Section: Introductionmentioning
confidence: 99%